MODEL KOMITMEN KARYAWAN BERBASIS JOB INSECURITY DAN KEPUASAN KERJA TERHADAP KEINGINAN BERPINDAH KERJA KARYAWAN BAGIAN PRODUKSI PADA PG. KA. TRANGKIL PATI - Ahmad Thoifurrohim (Jurnal Ekonomi dan Bisnis, 2017)
Substitution employees have positive and negative effects. However, most of the turnover brought unfavorable influence on the organization, namely the high level of turnover. The research aims to analyze the effects of job insecurity and job satisfaction of the desire to move production employees working with the commitment of employees as variable intervening. The population in this study is devoted only to permanent employees of the production of sugar factory. Kebon Agung Trangkil Pati. Referring to the formula Slovin and using purposive sampling techniques, the obtained sample size was 66 respondents. The results showed that job insecurity proved to be a significant negative effect on employee commitment, while job satisfaction has positive influence on employee commitment. Job insecurity is proven to have a positive and significant effect on turnover intentions work. Job satisfaction has a negative and significant impact on job turnover intentions. The results of the research commitment of employees are not able to become an intervening variable between job insecurity on job turnover intentions. Employee commitment to become intervening variable between job satisfaction and turnover intentions to work. The explanation can be interpreted that the higher the level of employee satisfaction, the more it will add to the high commitment of the employees to do something to support the company's success that it will reduce employees' desire to move work. Keywords: Job insecurity, job satisfaction, employee commitment and job turnover intentions.